2022
DOI: 10.1002/jbt.23201
|View full text |Cite
|
Sign up to set email alerts
|

Vitexin alleviates inflammation and enhances apoptosis through the regulation of the JAK/STAT/SOCS signaling pathway in the arthritis rat model

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory and autoimmune disorder. RA is progressive and needs long-term treatment. Vitexin is a naturally-occurring flavonoid that is identified in various plant sources. Vitexin is demonstrated to produce antioxidant effects with numerous pharmacological activities. This experimental in vivo study assessed the antiarthritic and apoptotic role of a natural plant extract, vitexin, on RA. Collagen-induced arthritis (CIA) rat model Sprague Dawley males were grouped into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 42 publications
(41 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, Vitexin also suppresses OA chondrocyte apoptosis via regulation of ER stress (Xie et al, 2018). Although the specific mechanism by which Vitexin regulates apoptosis in OA chondrocytes remains to be elucidated, recent studies have explored the relevant mechanisms under RA conditions and demonstrated that Vitexin has anti‐inflammatory and apoptotic activities by modulating JAK/STAT/SOCS signaling in a collagen‐induced arthritis rat model (Zhang, Ning, & Wang, 2022). Kong et al (2017) reported the promoting effect of the JAK/STAT/SOCS signaling pathway on IL‐10 production, which is well known as an anti‐inflammatory cytokine, and demonstrated that the activation of JAK/STAT/SOCS signaling also could be found in OA chondrocytes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, Vitexin also suppresses OA chondrocyte apoptosis via regulation of ER stress (Xie et al, 2018). Although the specific mechanism by which Vitexin regulates apoptosis in OA chondrocytes remains to be elucidated, recent studies have explored the relevant mechanisms under RA conditions and demonstrated that Vitexin has anti‐inflammatory and apoptotic activities by modulating JAK/STAT/SOCS signaling in a collagen‐induced arthritis rat model (Zhang, Ning, & Wang, 2022). Kong et al (2017) reported the promoting effect of the JAK/STAT/SOCS signaling pathway on IL‐10 production, which is well known as an anti‐inflammatory cytokine, and demonstrated that the activation of JAK/STAT/SOCS signaling also could be found in OA chondrocytes.…”
Section: Methodsmentioning
confidence: 99%
“…It can also increase the expression of epidermal growth factor in chickens on the 6th, 10th, and 15th day of heat stress, thereby reducing stressinduced intestinal mucosal damage [10][11][12][13][14]. As a natural polyphenol, vitexin, which is present in high concentrations in mung beans, hawthorn, and other foods, has a strong antioxidant activity [15] and has been widely used for the prevention and treatment of various diseases because of its functional and pharmacological activities [16]. It was shown that vitexin could alleviate heat-stress-induced apoptosis by upregulating antioxidant enzyme activities and endoplasmic reticulum-stress-mediated autophagy [17]; however, whether vitexin can relieve apoptosis induced by heat stress by regulating the ROS level and the heat shock protein expression has not been investigated.…”
Section: Introductionmentioning
confidence: 99%